Differences between several atherogenic parameters in patients with Controlled and Uncontrolled Type 2 Diabetes Mellitus (Faculty of Medicine Universitas Indonesia, 2010)
Aim to assess the differences between Atherogenic Index of Plasma (AIP), ratio of oxidized-Low Density Lipoprotein (Ox-LDL)/High Density Lipoprotein (HDL) and ratio of Lipoprotein-associated Phospholipase A2 (Lp-PLA2)/HDL in predicting the risk of coronary heart disease (CHD) in patients with controlled and uncontrolled type 2 Diabetes Mellitus (T2DM). Methods The study was done observationally with cross sectional design. A total of 80 patients, consisted of 40 controlled and 40 uncontrolled T2DM. The serum triglyceride (TG), HDL-C, Ox-LDL, Lp-PLA2 were examined in their relationship with T2DM risk. AIP is a ratio calculated as log (TG/HDL-C). Results AIP and ratio of Ox-LDL/HDL were significantly higher in uncontrolled than controlled T2DM (0.72 ± 0.13 vs 0.47 ± 0.22 , p < 0.001) and (1738.8 ± 625.5 vs 1418 ± 535.3, p = 0.02), but no significant difference was found in ratio of Lp-PLA2/HDL (5.09 ± 2.17 vs 5.95 ± 3.11, p = 0.16). Conclusion AIP and ratio of Ox-LDL/HDL value were significantly higher in uncontrolled than in controlled T2DM. These parameters may be beneficial in predicting the risk of atherosclerosis in diabetic patients. (Med J Indones 2010; 19:103-8)